PENGOLAHAN ARSIP PETA DAN DIGITALISASI ARSIP FOTO UDARA PADA SEKSI SURVEY PENGUKURAN DAN PEMETAAN DI KANTOR PERTANAHAN KABUPATEN KLATEN - , SETIAJI BASKARA SULENDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This report describes about arrangement of map archives and digitizing of aerial photo archives. On the first subject of arrangement of map archives have purpose to find out the process in arrangement of map archives. In addition the second purpose of arrangement of map archives is to get data about collection of map archives that exist in the institution. Then the purpose on second subject of digitizing of aerial photo archives have purpose for the manufacture of base map that used as a determination of the road layout and land in Klaten In this report the method of data collection by the author through three stages. The first stage is a method of interviews with sources who arrangement archival maps and have a ability to digitizing to get needed information. The second stage through the stages of observation and participation. Observations conducted by direct observation in the field to get the data as a final project report preparation. Participation is a method chosen by the authors to contribute in empowering thoughts, energy and time directly in in institution. Final data collection method is literature, this method is done to strengthen argument and obtain supporting data relevant to the topic that written by author. The conclusion of this report of arrangement of map archives and digitizing of aerial photo archives have not been optimally implemented. This is because arrangements of maps archives and digitizing of aerial photo archives requires precision so that its completion time is relatively long. There are still many obstacles encountered in arrangement of map archives and digitizing of aerial photo archives.